Daily field checking list by Walter Rosene, April 18, 1937 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Daily field checking list of birds observed in Boone County by Walter Rosene and Bernhard Nebbe, April 18, 1937. Also notes the young Great Horned Owl was quite well grown and well feathered. The nest also included several types of food. Plustek--flatbed